2017
DOI: 10.14233/ajchem.2017.20722
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Preformed Mixed Phase Graphene Sheets from Graphitized Sub-Bituminous Coal

Abstract: In present paper, a facile method is reported to extract mixed phase nanometre-sized carbon sheets from sub-bituminous coal. The lattice constants (La and Lc) of sub-bituminous coal were calculated to be 4.82 and 1.41 nm, respectively. The aromatic layers and average number of carbon atoms in the aromatic lamellae were estimated as 5 and 8, respectively. The obtained graphene sheets exhibits broadened D and G band in addition to a very broad 2D bump. Defect to graphitic ratio is found to be 0.54 indicating les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ethylene diaminetetraacetic acid being a chelating agent will form complexes with the majority of the metals such as aluminum and titanium. The formed complex was eliminated from the synthesized material by acid treatment which was applied to the complex solution, leaving behind the material of interest (Rao et al 2017). The XRD spectra presented in Figure 3 revealed that the diffractogram of the raw coal has 2θ° values stretching between 11° to 65°.…”
Section: Characterization Of Raw Coal and Synthesized Coal Graphene (Scg)mentioning
confidence: 99%
“…Ethylene diaminetetraacetic acid being a chelating agent will form complexes with the majority of the metals such as aluminum and titanium. The formed complex was eliminated from the synthesized material by acid treatment which was applied to the complex solution, leaving behind the material of interest (Rao et al 2017). The XRD spectra presented in Figure 3 revealed that the diffractogram of the raw coal has 2θ° values stretching between 11° to 65°.…”
Section: Characterization Of Raw Coal and Synthesized Coal Graphene (Scg)mentioning
confidence: 99%
“…The structural parameters are elucidated and depicted in Table-1. The typical 2θ values for the sp 2 carbon forms of the (002) planes occur at approximately 25°, which constitutes the π band. However, there is a marked broadening of the peak, which can be attributed to the γ band, formed due to aliphatic [2][3][4][5][6]. Lattice strain can also result in the broadening of the peak, but due to the small particle size, this effect is negligible.…”
Section: And Discussionmentioning
confidence: 99%